Analisis Bibliometric: Pemetaan Terhadap Modal Sosial Sebagai Instrument Pengentasan Kemiskinan dalam Pandangan Ekonomi Islam - Muhammad Abrar; Muhammad Herizal Ihza; Zulfan Adi Putra; Al-Munawir Al-Munawir; Safrirullah Safrirullah (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
Islamic economics uses the term "social capital" to describe social interactions and relationships based on values ​​such as charity, justice, cooperation and mutual trust. This study aims to map social capital as an instrument for poverty alleviation from an Islamic economic perspective. Descriptive research using bibliometric analysis and a quantitative approach is the methodology used. 1,130 papers constituted the population and sample investigated. The findings of this study show that, based on maps created using text data from previous mapping, researchers most frequently selected 7,415 terms and 222 research topics. This shows that there is a trend in studying social capital as a tool in the idea of ​​poverty alleviation from an Islamic economic perspective.